Vegetation structure and composition in the semi-arid Mapungubwe Cultural Landscape - P. Gandiwa; J. Finch; T. Hill (Global Journal of Environmental Science and Management)
Mapungubwe Cultural Landscape (MCL) woody vegetation was characterized to establish structural and compositional attributes. Stratified random sampling based on major soil types was used and nine plant variables were measured in 137(20x30) m2 sampling plots; these being genera, species and family names; basal circumference; plant height; depth and diameter of tree canopy; number of stems per plant; plant life status; number of trees and shrubs; and number of saplings. A total of 3114 woody plants were sampled, comprising an assemblage of 28 families, 63 genera and 106 species. The results suggest alluvial floodplain flanking the Limpopo River is a biodiversity hotspot with high plant species diversity (H’=1.8-2.2) 1/ha, taller trees (P